2006
DOI: 10.1111/j.1365-2311.2006.00775.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of maternal diet quality on offspring performance in the rove beetle Tachyporus hypnorum

Abstract: 1. The reproductive output of an individual is known to be influenced by diet quality, but the quality of the parent's diet can also influence the performance of the offspring. Dietary maternal effects may interact with the effects of the offspring's diet to produce a variety of response patterns.2. Maternal effects were investigated in a polyphagous predator, the rove beetle Tachyporus hypnorum , using three single-species diets: two low-quality diets consisting of the aphids Sitobion avenae and Rhopalosiphum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
1
39
0
2
Order By: Relevance
“…Larger eggs are generally associated with larger adults and greater survival of both larvae and adults (Fleming and Gross 1990;Fox 1994;. Females may modify their reproductive allocation, adjusting the number of eggs laid or egg size according to nutritional resources available in the maternal environment (Rotem et al 2003;Kyneb and Toft 2006) or in response to host quality (Fox et al 1997). Because the maternal reproductive effort should be divided optimally between the two fitness components, egg size and fecundity, the oviposition patterns may be affected by a trade-off between these two traits (Smith and Fretwell 1974;Messina and Fox 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Larger eggs are generally associated with larger adults and greater survival of both larvae and adults (Fleming and Gross 1990;Fox 1994;. Females may modify their reproductive allocation, adjusting the number of eggs laid or egg size according to nutritional resources available in the maternal environment (Rotem et al 2003;Kyneb and Toft 2006) or in response to host quality (Fox et al 1997). Because the maternal reproductive effort should be divided optimally between the two fitness components, egg size and fecundity, the oviposition patterns may be affected by a trade-off between these two traits (Smith and Fretwell 1974;Messina and Fox 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal effects have been demonstrated to impact several fitness components of offspring in a range of species, including effects on birth weight or egg size (e.g., humans and chimpanzees, Fessler et al, 2005; zebra finch, Gilbert et al, 2006; rove beetle, Kyneb and Toft, 2006; soil mites, Plaistow et al, 2006;fish, Taborsky, 2006;lizard, Warner et al, 2007), growth rate and age at maturity (e.g., mandrills, Setchell et al, 2002; savanna baboons, Altmann and Alberts, 2005; beetles, Kyneb and Toft, 2006;mites, Plaistow et al, 2006), and longevity or probability of survival (e.g., mandrills, Setchell et al, 2006; fruit flies, Priest et al, 2002; herring gulls, Bogdanova et al, 2006;turtles, Paitz et al, 2007). These effects also impact the development of competitive traits such as aggression and mounting behavior (Dloniak et al, 2006;Forstmeier et al, 2004;Royle et al, 2005), and both song rate and mate choice (Forstmeier et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The fitness of an individual is known to be influenced by its diet; the quality of the parent's diet can also greatly affect the performance of the offspring (Kyneb and Toft 2006). Outdoors, we found that starved mothers produced offspring that developed for longer, while indoors the trend was opposite.…”
Section: Discussionmentioning
confidence: 92%